FORMULATION AND EVALUATION OF EXTENDED RELEASE PELLETS OF PIOGLITAZONE HYDROCHLORIDE USING NATURAL AND SYNTHETIC POLYMERS BY FLUIDIZED BED COATING TECHNIQUE - B, GOWTHAMI; S, NIHITHA; NAGAM, SANTHI PRIYA; NADENDLA, RAMA RAO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the current work was to develop Pioglitazone hydrochloride (HCl) pellets coated with natural polymer extracted from peas gum and also to compare the drug release profile with coatings containing semi-synthetic and synthetic polymers. Methods: Fluidized bed coating technique was used to develop pellets. A 22 factorial design was employed to study the effect of independent variables (inlet air temperature and spray rate), on dependent variables (percentage entrapment efficiency, percentage friability, and average particle size). Optimization was done by fitting experimental data to the software program. Obtained pellets were subjected to different evaluation parameters which are critical in the development of the dosage form. An in vitro lag phase study was carried out for all batches in simulated gastric fluid (0.1N HCl) for 5 h and in vitro drug release study was carried out for optimized batch (E-2 and P-3) in simulated intestinal fluid (pH 7.4 phosphate buffer). Results: The optimized batches E-2 and P-3 showed satisfactory percentage entrapment efficiency of 92.66±1.52, percentage friability of 0.57±0.03, and average particle size of 1424±16 μm. All batches maintained lag phase for 5 h in 0.1N HCl. An optimized batch of two different sizes exhibited a burst release within 30 min in a simulated intestinal fluid with no significant difference in release rate constant (*p>0.05) and followed first-order kinetics. Conclusion: Thus, Pioglitazone HCl pulsatile pellets were successfully developed for treating diabetes mellitus by fluidized bed coating technique employing factorial design.